Modelling optimal cropping, risk and constraints to livelihood among smallholder farmers in North-East Nigeria (NEN) - Peter, Emmanuel (2024)
Agriculture is the main employer of labour and plays a vital role in the Nigerian economy. The Nigerian agricultural sector is dominated by smallholder farmers who, not only depend on their land as a source of food and income but also produce most of the food consumed in Nigeria. However, these smallholder farmers face many challenges, particularly socio-economic constraints and uncertainty associated with variability of yields and prices. There is also the challenge of farm inputs price variability and concern for personal safety in the region, which altogether obstructs productivity for improved livelihood. The Northern region accounts for an approximate two-thirds of the total smallholder farmers in Nigeria, who face similar constraints and risk exposure.